The Effect of Personal Selling and Skills on Consumer Interest in Nuriza Mart in Meureudu District, Pidie Jaya Regency - Teuku Isnaini; Cut Yusnidar; Nadia Nadia (Budapest International Research and Critics University, 2022)
This study aims to determine